Tantangan Guru dalam Mengembangkan Nalar Kritis Siswa untuk Menjawab Soal-Soal Asesmen Kompetensi Minimum (AKM) - Laila Fajriyanti; Rizki Hikmawan; Nuur Wachid Abdul Majid (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The transition from education policy, namely the National Examination to a Minimum Competency Assessment, requires adaptive learning habits for teachers and students. The UN culture which focuses on how students face tests or exams is transitioning to AKM which views regular evaluation as an important part of improving the teaching and learning process, especially in the aspect of critical thinking. One important component to achieve accurate assessment results is adjusting learning methods. This research aims to determine the challenges and attitudes taken by teachers in facing assessments. This research uses a qualitative approach with data collection methods using interviews for teachers and questionnaires for students. Researchers want to know teachers' understanding of AKM, analyze the influence of the learning methods used on aspects of critical reasoning and find types of learning methods that can help with this problem. The research results show that there are no special changes to learning methods in responding to changes in assessment.